Is Thermal Pulsation Therapy Effective for Dry Eyes Before and After Cataract Surgery? A Systematic Review and Meta-Analysis - Chen KY; Chan HC; Chan CM (Clinical Ophthalmology)
Kai-Yang Chen,1 Hoi-Chun Chan,2 Chi Ming Chan3,4 1Department of Medicine, School of Medicine, College of Medicine, Taipei Medical University, Taipei, Taiwan; 2Department of Pharmacy, School of Pharmacy, China Medical University, Taichung, Taiwan; 3Department of Ophthalmology, Cardinal Tien Hospital, New Taipei City, Taiwan; 4Department of Ophthalmology, School of Medicine, Fu Jen Catholic University, New Taipei City, TaiwanCorrespondence: Chi Ming Chan, Email 068268@mail.fju.edu.tw; m212092001@tmu.edu.twBackground: Meibomian gland dysfunction (MGD) is a primary cause of evaporative dry eye disease (DED), which is often exacerbated by cataract surgery due to surgical trauma and inflammation. Thermal pulsation therapy (TPT) aims to enhance meibomian gland function and relieve dry eye symptoms. We conducted a systematic review and meta-analysis to evaluate the effectiveness of TPT in managing dry eye symptoms associated with cataract surgery.Methods: A systematic search was performed in December 2024 across PubMed, ScienceDirect, CINAHL, and the Cochrane Central Register of Controlled Trials to identify original research on the efficacy of TPT in addressing cataract surgery-related dry eye symptoms. The quality of the included studies was evaluated using the Risk of Bias in Non-Randomized Studies of Interventions tool, with results visualized through the Robvis 2.0 tool developed by the Cochrane Collaboration.Results: The search yielded 365 records, of which seven studies met the inclusion criteria for this meta-analysis. Key outcomes analyzed included the meibomian gland yielding liquid secretion (MGYLS) score, tear break-up time (TBUT), ocular surface disease index (OSDI) score, and lipid layer thickness (LLT). The meta-analysis revealed a moderate effect of TPT, with a small but clinically significant improvement observed in MGYLS scores (Cohen’s d = 0.29, p = 0.033) and TBUT (Cohen’s d = 0.15, p = 0.029). However, the effects on OSDI scores and LLT were not statistically significant. Study heterogeneity varied, with some outcomes exhibiting considerable variability.Conclusion: TPT provides moderate and clinically meaningful improvements in MGYLS scores and TBUT for patients experiencing dry eye symptoms after cataract surgery, although improvements in OSDI scores and LLT did not achieve statistical significance. The variability in study quality and heterogeneity highlights the need for well-designed, high-quality research to confirm these findings and evaluate the durability of TPT’s therapeutic effects both before and after cataract surgery.Synopsis: This study investigated if thermal pulsation therapy (TPT) helps with dry eye symptoms after cataract surgery. The analysis of existing research suggests TPT improves tear quality and meibomian gland function, potentially improving patient comfort after cataract surgery.Keywords: thermal pulsation therapy, dry eye symptoms, cataract surgery, meibomian gland dysfunction, systematic review, meta-analysis